Retraction notice to "P02. Predicting the outcome of post-anoxic comatose patients based on single-trial EEG analysis Clin Neurophysiol 125 (2014) e43–e44. Issue 3 (March 2015) - Simonin, A.; Tzovara, A.; Cossy, N.; Rossetti, A.; Oddo, M.; de Lucia, M.
<x xml:space="preserve">Abstract</x> This Abstract has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy). This Abstract has been retracted at the request of the co-authors due to the fact that the Abstract was prepared and submitted by a single author, without the agreement of other co-authors, includes several mistakes and potentially conflicts with another publication.